Effects of water and temperature variations on deformation of limestone aggregates, cement paste, mortar and High Performance Concrete (HPC). (August 2016) - Cagnon, H.; Vidal, T.; Sellier, A.; Soula, C.; Bourbon, X.; Camps, G.
Abstract: The present paper deals with the dimensional variations of limestone aggregates, cement paste, mortar, and High Performance Concrete (HPC) made with these constituents, when subjected to temperature changes in drying and sealed conditions. Variable water contents are studied for each material. The overall experimental results were obtained using strain gauges and Digital Image Correlation technique (DIC) is also applied for one configuration test. A significant difference between coefficients of Thermal Expansion (CTE) of cement paste and aggregate is observed, which leads to a large differential thermal deformation, able to explain thermal damage for temperatures between 50 °C and 100 °C. Water content has a great influence on material thermal dilation, causing delayed deformations especially for temperatures above 60 °C and for initially saturated samples. These experimental data may allow Thermo-Hydro-Mechanical models to be improved so that the in-situ long term behaviour of concrete can finally be predicted. The results confirm the dilation coefficient contrast between paste and aggregate, and also show that this contrast is markedly affected by the drying conditions and the initial state of saturation.